Cantharidin Inhibits Proliferation of Liver Cancer by Inducing DNA Damage via KDM4A-Dependent Histone H3K36 Demethylation. (11th July 2022) - Wei, Chao; Deng, Xiangui; Gao, Shudi; Wan, Xuemei; Chen, Jing
Abstract : Objective . To investigate the effect of cantharidin on DNA damage in hepatocellular carcinoma cells and its possible mechanism. Methods . Cell proliferation assay and terminal deoxynucleotidyl transferase-mediated dUTP nick end labeling (TUNEL) assay were used to analyze the effects of cantharidin on cell proliferation and apoptosis of hepatocellular carcinoma cells. The expression levels of DNA damage markers H2AX and P21 were analyzed by qRT-PCR. The expression of KDM4A and H3K36me3 was observed by western blot. The expression of KDM4A was regulated by siRNA or plasmid transfection. The effect of KDM4A on DNA damage induced by cantharidin in liver cancer was observed after overexpression and addiction of KDM4A. Results . Cantharidin can significantly inhibit the growth of hepatocellular carcinoma cells and induce apoptosis of hepatocellular carcinoma cells. Cantharidin enhances the chemotherapy sensitivity of liver cancer by targeting the upregulation of KDM4A and the regulation of DNA damage induced by H3K36me3. Overexpression of KDM4A enhances DNA damage induced by cantharidin in HCC. KDM4A silencing attenuated the damage of cantharidin to the DNA of HCC cells. Conclusion . Cantharidin can inhibit the growth and promote apoptosis of hepatocellular carcinoma cells. Meanwhile, cantharidin can induce DNA damage in HCC cells. Mechanism studies have shown that cantharidin induces DNA damage through the demethylation of KDM4A-dependent histone H3K36.